The Effectiveness of Macromedia Flash Digital Media in Improving Students’ Mathematics Reasoning - Muhamad Yunus; Mizan Abrory; Dedek Andrian; David Maclinton; Zafrullah (Mathematics Research and Education Journal, 2022)
This study aims to describe the effectiveness of students' mathematical reasoning abilities through Macromedia flash digital learning media. Learning media is an educational product that can bridge students' interest in learning mathematics so that with this interest, they can increase their mathematical thinking skills at a higher level. The population of this study was students of SMPN Rokun Hulu. The research sample was one of the junior high schools in Rokan Hulu Regency, which was selected purposively according to the problems found in the field, namely SMPN 1 Ujungbatu. The research instrument is an essay test. Research data analysis using quantitative descriptive data analysis, correlational, and paired t-test. The results showed that there was a significant difference between ordinary learning used by teachers and learning using Macromedia flash digital media. These results can be seen from the results of the descriptive test and paired t-test with a significance of 0.00. These results indicate that Macromedia flash-based digital learning media effectively improves the reasoning of SMPN 1 Ujungbatu students